Growth and value effect on Jakarta Islamic Index: analysis towards performance of Sharia equity mutual fund - Rusmita, Sylva Alif; Che Mohd Salleh, Marhanum; Sukmaningrum, Puji Sucia, Siti Zulaikha (State Islamic University Syarif Hidayatullah Jakarta, 2019)
This study provides evidence that value and growth stocks are able to explain Net Asset Value of sharia mutual fund. Growth and value stocks in 2013-2017 are used to predict mutual fund profits. Thus, prior to any losses or lower Net Asset Value experienced by customers, investment managers and investors can estimate the profit or loss obtained. This study uses quantitative method with the latest secondary data from companies indexed in the Jakarta Islamic Index and sharia mutual fund data. The results of statistical tests show that growth and value shares equally affect the profit of sharia mutual funds. The growth stock has a larger R-Square than stock value. Meanwhile, the ratios that most affect Net Asset Value of sharia mutual fund are the Return on Equity and Book to Market Value.